Ensino de respostas variadas de brincar de faz de conta para crianças com TEA - Carvalho, Fabiana de Godoi (2021)
Children diagnosed with autism spectrum disorder (ASD) show rigid and stereotyped behavior patterns, especially those involving pretend play, which is very present in the children’s repertoire. The repertoire of playing is an operant behavior maintained by the consequences. It can be fundamental for the teaching of new repertoires for the child. Several studies indicate that variability is a factor that must be considered in the teaching procedures of such behavior, besides teaching the topography of the game. Therefore, this study aimed: (1) to promote the teaching of new responses, which were scripted from the video modeling; and (2) to promote behavioral variability of responses with progressive LAG. This study verified the emission of responses taught by the video, as well as varied responses that were not scripted, and the emission of stereotyped responses for two children diagnosed with ASD, through the manipulation of five experimental conditions. Phase 1 functioned as a baseline measure of motor and verbal responses to the pretend play repertoire. Phase 2 consisted of teaching six responses from a video modeling procedure. Phase 3 worked as a survey to measure the behaviors taught from the video. Phase 4 manipulated the progressive LAG reinforcement scheme to produce the variability of motor and verbal responses. Finally, Phase 5 occurred as a follow-up 30 days after the end of the variability phase. As a main result, the video modeling promoted the teaching of new responses. For one of the participants, it worked to promote variability. For another participant, the progressive LAG scheme worked at was essential for teaching varied responses. Themes and manipulations for future studies are discussed